Motivasi Wanita Pasangan Usia Subur (PUS) dalam Menggunakan Alat Kontrasepsi Intrauterine Device (IUD) di Kecamatan Sukorejo Kota Blitar - Sunarti Sunarti; Anis Anis (STIKes Patria Husada Blitar, 2017)
The fertile age couples (FAC) motivation in controling pregnancy, which one using IUD contraception. The largest acceptors of 27.1% FAC women of the total FAC women in district Sukorejo 2014 using the IUD. The purpose of the study was to describe the motivation of women in Fertile Age Couples (FAC) in using IUD in district Sukorejo Blitar. The researcher using descriptive method. The data will be taken from FAC women who use IUD in district Sukorejo, Blitar, total sample as much as 44 FAC women using Purposive Sampling technique. Data collection will be done by giving questionnaires. Time data retrieval from March to April 2016. The research results obtained by the motivation that is high motivation 72.7% and is enough motivation 27,3%. Intrinsic motivation is high especially at desire from her self and the target to get effectiveness usage of IUD. Extrinsic motivation also high especially support of environment. And distressed motivation is enough especially at body weight that affects FAC women to use IUD contraception. From this research, the researcher recommended to maintain high motivation in PUS women to use IUD contraceptives method.